A Rare Presentation Characterized by Epileptic Spasms in ALDH7A1, Pyridox(am)ine-5′-Phosphate Oxidase, and PLPBP Deficiency - Jiao, Xianru; Gong, Pan; Niu, Yue; Zhang, Yuehua; Yang, Zhixian (Frontiers in Genetics, 2022)
Objective: To analyze the clinical feature, treatment, and prognosis of epileptic spasms (ES) in vitamin B6–dependent epilepsy, including patients with pyridoxine-dependent epilepsy (PDE) caused by ALDH7A1 mutation, pyridox(am)ine-5′-phosphate oxidase (PNPO) deficiency, and PLPBP deficiency. Methods: We analyzed data from a cohort of 54 cases with PDE, 13 cases with PNPO deficiency, and 2 cases with PLPBP deficiency and looked for the presentation of ES among them. Results: A total of 11 patients with the seizure presentation of ES have been collected. Among them, four patients carried mutations in ALDH7A1, six carried mutations in PNPO, and the remaining one carried mutation in PLPBP. The analysis of this cohort identified nine cases presenting as infantile spasms distributed in the three diseases and two cases presenting as Ohtahara syndrome diagnosed with PDE and PNPO deficiency, respectively. In the PDE and PLPBP deficiency groups, seizures were controlled by pyridoxine monotherapy, and the remaining one had refractory seizures due to secondary brain atrophy. In the groups with PNPO deficiency, one patient showed seizure-free when treated by PLP combined with valproic acid, three still had infrequent seizures treated by PLP monotherapy or pyridoxine or PLP combined with other antiseizure medications, and two died. In two cases presenting as Ohtahara syndrome, after regular treatment, one showed seizure-free, the others showed a marked decrease in seizure frequency, and they both showed an improvement in EEG. Significance: ES might be a common form of seizures in PNPO deficiency, and EEG presented as hypsarrhythmia or a burst suppression pattern. It is difficult for pyridoxine to control frequent seizures caused by secondary brain injury. In our PNPO deficiency cohort, patients with infantile spasms did not respond better to PLP than pyridoxine. Timely and correct treatment could prevent the transformation of the child’s disease from Ohtahara syndrome and infantile spasms to subsequent epileptic encephalopathy or refractory epilepsy.